A novel strategy of polystyrene acrylate – Polysiloxane core-shell emulsion for surface protection of cementitious materials. (October 2022) - Wu, Cong; Yin, Bing; Hou, Dongshuai; Li, Shaochun; Wang, Xinpeng
Abstract: Core-shell polymer coating is a significant means of improving the surface protection of cement-based materials. In this paper, a novel strategy for the paraffin-doped polystyrene acrylate-polysiloxane core-shell emulsions (CSP) are proposed by combining polyaddition and polycondensation reactions, integrating the superior corrosion-resistance of PSA emulsions with the high-hydrophobicity of siloxane emulsions. The CSP emulsions have excellent physical stability and rheological behavior, with a lower proportion of unsaturated bonds and lower content of chemically bound water. The core-shell structure promotes the formation of Si–O bonds between the polymer molecules and the cement matrix, and more conducive to the formation of new silicate crystals on the cement hydrate surface. Macroscopically, the surface energy of the cement samples treated with CSP coating is below 16.7 mJ/m 2, while its superficial nanoscale papillae give a water contact angle of almost 140°. The capillary absorption coefficient of the Portland concrete treated with CSP coating can be decreased to only 2.09 g/(m 2 ·h 0.5 ). Meanwhile, the corrosion rate of Cl − and SO4 2− on the cementitious materials are significantly inhibited by the CSP membrane, reducing the levels of Friedel's salt, ettringite and gypsum generated by ionic corrosion, respectively. Furthermore, the CSP membranes have excellent molecular structural integrity and high cross-linkage under acid/alkaline corrosion and photo-thermal aging, maintaining superior adhesion and corrosion resistance with the cement substrate.